The Urgency Of Implementing Some Of The Effective Arabic Learning Methods To Improve The Students’ Ability To Read “KITAB KUNING” Of PBA FTIK Program Of IAIN Palu - Ahmad Asse; Ahmad Sehri; Prof. M. Asy'ari (IAIN Padangsidimpuan, 2020)
This research is focused, how to apply several effective Arabic learning methods in improving the ability to read the Kitab Kuning to the Students PBA IAIN Palu. This research is a field research, which provides a systematic description of situations and events, intact and actual, and explain the relationship of the problem being studied. Data collection techniques with field studies, in-depth interviews and observations. The data obtained in the field are then analyzed and compiled in a draft question and answer between the researchers who then make general conclusions to be reported as a result of the research that has been done. The results of this study indicate that the application of several methods among the students of IAIN Palu is not effective except for the qawaid tarjamah method, as mandated in the 1998 curriculum. There is no meeting point between the curriculum and curriculum implementers, in this case the lecturers who are the main factor in not implementing the method according to expectations. While the qawaid tarjamah method is more effective than other methods. In addition, the language skills and reading of the Kitab Kuning owned by IAIN Palu students are very standardized even though the qawaid tarjamah method is very fruitful but not optimal. This is due to the application of the direct method using the Nazariyah al-Wahdah theory, but there is no stability in reading and translating.